ANALYZING EFL UNIVERSITY STUDENTS’ READING NEEDS FOR DIGITAL FLIPBOOKS IN ENGLISH LEARNING - Efa Silfia; Yetti Zainil; Muhhammad Al Hafizh (English Study Program University of Pasir Pengaraian, 2026)
This study investigated EFL university students’ reading needs toward the use of digital flipbooks as learning materials. It aimed to identify students’ needs, wants, and preferences regarding digital reading resources, as well as their expectations. A descriptive quantitative design supported by qualitative responses was employed involving 41 students from the second, fourth, sixth, and eighth semesters. Data were collected through a questionnaire using a five-point Likert scale and open-ended questions and were analysed using percentages, mean scores, and descriptive analysis. The findings indicated that students demonstrated strong needs for accessible and flexible digital reading materials, with necessities obtaining the highest mean score (M = 4.06). Smartphone-based access was the most preferred mode of learning (M = 4.50), while multimedia-supported features were positively valued (M = 3.75).Vocabulary limitations and reading comprehension difficulties remained the main challenges (M = 3.19), indicating the need for materials that provide structured support and interactive practice. Students also preferred guided reading activities, including comprehension and vocabulary-based exercises (M = 3.67). The study highlights the importance of designing digital flipbooksthat align with learners’ actual reading needs to enhance engagement and comprehension. These findings provide practical implications for developing interactive and pedagogically appropriate digital reading materials for EFL learning in higher education.